PELAKSANAAN PROSES PENUNTUTAN PERKARA TINDAK PIDANA KORUPSI DI KEJAKSAAN TINGGI JAWA TENGAH - Galih Hartanto Putro, Sukinta, Bambang Dwi Baskoro (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Corruption in Indonesia is still going and continues to increase. Development continues to increase from year to year, both in number of cases and the amount of financial loss to the state and in terms of the quality of criminal offenses committed more systematic and scope to enter all aspects of society. Corruption in Indonesia has also been extended to various sectors. The human body is like a